2020
DOI: 10.3390/agronomy10070997
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Response of Oakleaf Lettuce Seedlings to Different Concentrations of Some Metal(oid) Oxide Nanoparticles

Abstract: Nanoparticles (NPs) significantly modify the physiological functions and metabolome of plants. The purpose of the study was to investigate the effect of CeO2, Fe2O3, SnO2, TiO2, and SiO2 nanoparticles, applied in foliar spraying of oakleaf lettuce at concentrations 0.75% to 6%, on the antioxidant enzyme activity and content of non-enzymatic antioxidants, chlorophyll pigments, fresh weight (FW) and dry weight (DW). It was found that 3% Fe2O3-NPs caused a 27% decrease in fresh weight compared to control plants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
1
23
1
Order By: Relevance
“…A statistical analysis of the main effect means confirmed the elevated content of L-ascorbic acid in NPs treated plants. In a previous study, where higher concentrations of TiO 2 -NPs were applied (1.5%; 3%; 6%) to the oakleaf lettuce plants, we also observed an elevated level of L-ascorbic acid when compared with the control [ 30 ]. Similarly, Silva et al [ 55 ] found (for wheat) an increase in the levels of this compound for all TiO 2 -NP treatments (5, 50, and 150 mg·L −1 ).…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…A statistical analysis of the main effect means confirmed the elevated content of L-ascorbic acid in NPs treated plants. In a previous study, where higher concentrations of TiO 2 -NPs were applied (1.5%; 3%; 6%) to the oakleaf lettuce plants, we also observed an elevated level of L-ascorbic acid when compared with the control [ 30 ]. Similarly, Silva et al [ 55 ] found (for wheat) an increase in the levels of this compound for all TiO 2 -NP treatments (5, 50, and 150 mg·L −1 ).…”
Section: Resultsmentioning
confidence: 58%
“…The opposite trend was observed at t5, when the control lettuce had slightly more FW and DW than TiO 2 -NPs treated plants, but this was not confirmed statistically. Summing up, the influence of TiO 2 -NPs on oakleaf lettuce growth turned out to be relatively small, as in an earlier experiment, with higher concentrations of TiO 2 -NPs (1.5–6%), no significant changes occurred in FW and DW, in comparison with the control seedlings [ 30 ].…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations